The Role of Intraoperative MRI in Awake Neurosurgical Procedures: A Systematic Review - Chowdhury, Tumul; Zeiler, Frederick A.; Singh, Gyaninder P.; Hailu, Abseret; Loewen, Hal; Schaller, Bernhard; Cappellani, Ronald B.; West, Michael (Frontiers in Oncology, 2018)
Background- Awake craniotomy for brain tumors remains an important tool in the arsenal of the treating neurosurgeon working in eloquent areas of the brain. Furthermore, with the implementation of intraoperative magnetic resonance imaging (I-MRI), one can afford the luxury of imaging to assess surgical resection of the underlying gross imaging defined neuropathology and the surrounding eloquent areas. Ideally, the combination of I-MRI and awake craniotomy could provide the maximal lesion resection with the least morbidity and mortality. However, more resection with the aid of real time imaging and awake craniotomy techniques might give opposite outcome results. The goal of this systematic review.is to identify the available literature on combined I-MRI and awake craniotomy techniques, to better understand the potential morbidity and mortality associated. Methods- MEDLINE, EMBASE and CENTRAL were searched from inception up to December 2016. A total of 10 articles met inclusion in to the review, with a total of 324 adult patients. Results- All studies showed transient neurological deficits between 2.9 percent to 76.4 percent. In regards to persistent morbidity, the mean was approximately 10 percent (ranges from zero to 35.3 percent) with a follow up period between 5 days to 6 months. Conclusion- The preliminary results of this review also suggest this combined technique may impose acceptable post-operative complication profiles and morbidity. However, this is based on low quality evidence, and is therefore questionable. Further, well-designed future trials with the long-term follow-up are needed to provide various aspects of feasibility and outcome data for this approach.